PERBANDINGAN PENAMBAHAN KUNYIT DAN PUTIK KEPALA TERHADAP HASIL JADI HENNA DAUN PACAR - Afrilla Ulfa; Merita Yanita (Jurnal Tata Rias dan Kecantikan, 2022)
Utilization of natural dyes for cosmetics becomes one of the alternatives to chemical dyes. Because these chemical dyes can cause irritation to the skin even the color owned by chemical dyes can not stand stored for a relatively long time. This study aims to a) analyze the color name (Hue) and color brightness (Value) of the use of henna leaves (Lawsonia inermis) and turmeric as a color light produced in the use of time 3 hours, 5 hours, 7 hours on the palm and fingertips, b) analyze the color name (Hue) and color brightness (Value) of the use of henna leaves (Lawsonia Inermis), turmeric and coconut pistils produced in the use of 3 hours , 5 hours, 7 hours on the palm and fingertips and c) analyze the color comparison (Hue) and color brightness (Value) resulting from henna and turmeric leaves with henna leaves, turmeric and coconut pistils on the palms and fingertips. This type of research is quasy experiment. The population of this study was a student of Padang State University class of 2016 aged 20-25 years with 3 samples and 7 panelists. Data retrieval technique is purposive sampling method. Descriptive data analysis techniques by displaying statistics and frequency. with independent sample- t-test  confidence. Based on the results of the study on the addition of turmeric from the average color aspect of 2.71 good categories and aspects of color brightness (value) an average of 3.14 good categories. In the use of the addition of coconut pistil henna from the average color aspect of 2.80 good categories and aspects of color brightness (value) on average 2.9 good categories and in the color indicator (hue) there is no difference in the influence of the finished result of henna making henna leaves with the addition of turmeric and the addition of coconut pistils. Value p = 0.812 (p>0.05) and in the color brightness indicator (value) there is no difference in the influence of henna making henna leaves with the addition of turmeric and the addition of coconut pistil henna. Value p= 0.531 (p>0.05). Conclusion on the color indicator (hue) there is no difference in the influence of the finished result of henna making henna leaves with the addition of turmeric and the addition of coconut pistils and in the indicator of color brightness (value) there is no difference in the influence of the result of making henna henna henna leaves with the addition of turmeric and the addition of coconut pistil henna and recommended for further research on the manufacture of henna henna leaves with the addition of turmeric and the addition of coconut pistils more , so it is expected that the color acquisition is better than before.